Technology of virtual reality video processing and streaming - Zhenjiang DONG; Dongzhuo ZHANG; Cheng HUANG; Haijun LIU (Dianxin kexue)
Virtual reality is a hot topic in the field of video.The current situation of VR video content production and VR video display technology was introduced,and the key technologies of viewport dependent VR video processing were analyzed.Finally,the mechanisms of VR video streaming and corresponding network requirements were discussed.